Investigation On Antiproliferative Mechanisms Of Alstonia Angustiloba- Silver Nanoparticles In Skin Squamous Cell Carcinoma - Ab Rahim, Nurhidayah (2023)
Traditional methods of nanoparticles synthesis frequently use toxics chemicals and substantial energy, which may have detrimental effects on the environment and human health. Recently, plant-based synthesis of nanoparticles (AgNPs) has emerged as a promising green synthesis method. Herein, we reported the green synthesis of AgNPs using the aqueous extract of A. angustiloba leaves and assessed its antiproliferative mechanisms. Initially, the physiochemical properties of A. angustiloba-AgNPs were characterised using UV–Vis spectrophotometry, FT-IR, FESEM, EDX, TEM, XRD and zeta sizer analyses. The cytotoxicity of A. angustiloba-AgNPs was examined by MTT assays against the A431 cancer cell line. The morphology of the treated cells was examined using fluorescence microscopy and the antiproliferative mechanisms of the nanoparticles in A431 cells were investigated by annexin-FITC/propidium iodide (PI) staining and DNA cell cycle analysis using flow cytometry. The intracellular ROS levels were measured using a commercially available kit. The expression of apoptosis and cell cycle-related proteins was determined by Western blotting. The results of SEM and TEM revealed that the nanoparticles showed a spherical shape with the highest particle size distribution was 11 to 14 nm, while a mean hydrodynamic size of 61.21 ±3.96 nm and a zeta potential value of –18.67 ±3.12 mV that was measured by DLS. Besides that, the XRD pattern showed that metallic Ag has a face-centred cubic structure with the diffraction peak values at 2θ of 38.11°, 44.26°, 64.29°, and 77.07° corresponding to lattice planes at (111), (200), (220), and (311), respectively. FTIR results revealed the presence of –OH, C=C and C-O may serve as a capping and stabilising agent. The nanoparticles inhibited the growth of A431 cells with an IC50 value of 39.58 μg/mL after 72 h of treatment. Meanwhile, the IC50 values for extract alone and commercial AgNPs were 164.3 ug/ml and 16.89 ug/ml, respectively. Further investigation has shown that the nanoparticles induced both apoptosis and cell cycle arrest at S-phase in A431 cancer cells. Western blotting analysis revealed that A. angustiloba-AgNPs decreased the expression of Bcl-2 while increasing the expression of cleaved caspase-3, 9 and Bax. Moreover, the downregulation of cyclin E protein indicated impaired progression in the S phase of the cell cycle. In summary, A. angustiloba-AgNPs inhibit cell proliferation and promote apoptosis in A431 cancer cells through increasing intracellular ROS production and activating the caspase-dependent apoptotic pathway and cell cycle arresting. These preliminary findings provided an insight that A. angustiloba-AgNPs have high anti-neoplastic potential, therefore further pharmacological studies should be conducted to unveil its attractiveness as an anticancer agent.